2010
DOI: 10.1515/mamm.2010.019
|View full text |Cite
|
Sign up to set email alerts
|

Diet composition ofGracilinanus agilis(Didelphimorphia, Didelphidae) in dry woodland areas of Cerrado in central Brazil

Abstract: No abstract available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 2 publications
1
6
1
5
Order By: Relevance
“…For this reason, the insectivorous-omnivorous alimentary habits of certain mammals such as the marsupial G. agilis may facilitate infection by spirurid nematodes (Bocchiglieri et al, 2010). This finding was corroborated by our previous studies that showed a high prevalence of spirurids in G. agilis from the Pantanal region in Brazil, most likely due to their arboreal and insectivorous diet (Lopes Torres et al, 2009).…”
Section: Introductionsupporting
confidence: 76%
“…For this reason, the insectivorous-omnivorous alimentary habits of certain mammals such as the marsupial G. agilis may facilitate infection by spirurid nematodes (Bocchiglieri et al, 2010). This finding was corroborated by our previous studies that showed a high prevalence of spirurids in G. agilis from the Pantanal region in Brazil, most likely due to their arboreal and insectivorous diet (Lopes Torres et al, 2009).…”
Section: Introductionsupporting
confidence: 76%
“…Da mesma forma, se consideramos a polpa e fi bras derivadas dos frutos de Melastomataceae, cuja coloração é tipicamente azul-arroxeada, a freqüência de consumo para esta família aumenta para cerca de 82%. Esses são os maiores valores encontrados para freqüência no consumo de frutos não só para a espécie G. agilis, como também para esse gênero de marsupial (ver Martins et al 2006;Lessa & Costa 2009;Bocchiglieri et al 2010). Nossos dados parecem estar mais de acordo com os estudos realizados por Astúa de Moraes et al Em relação aos frutos consumidos por G. agilis, verificamos que esse marsupial consome basicamente frutos de plantas pioneiras, as quais estiveram presentes em 84,4% das fezes que continham sementes.…”
Section: Discussionunclassified
“…Abundance peaks were detected in April 2010 (wet season), including the record of early reproductive onset that would be related to the production of more than one litter in the favorable season of the year and had already been observed for D. albiventris in another biome (Astúa and Geise 2006). Gracilinanus agilis is a small arboreal marsupial, often associated with forested habitats, and with an insectivorous/omnivorous diet (Bocchiglieri et al 2010;Reis et al 2011). Apparently there are no Delciellos | Mammals of Caatinga previous studies about its population dynamics in other areas of Caatinga.…”
Section: Discussionmentioning
confidence: 99%